2002
DOI: 10.1046/j.1365-2168.2002.02168.x
|View full text |Cite
|
Sign up to set email alerts
|

Complications of radiofrequency coagulation of liver tumours

Abstract: Background: Radiofrequency coagulation (RFC) is being promoted as a novel technique with a low morbidity rate in the treatment of liver tumours. The purpose of this study was to assess critically the complication rates of RFC in centres with both large and limited initial experience, and to establish causes and possible means of prevention and treatment. The morbidity and mortality of RFC, while low, is higher than previously assumed. With adequate knowledge, many complications are preventable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
475
7
16

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 650 publications
(519 citation statements)
references
References 111 publications
(263 reference statements)
21
475
7
16
Order By: Relevance
“…No other early post operative deaths were encountered during the study or until the time of writing. The 30-day mortality rate observed in this study is again at least comparable to other similar studies using RF and Cryotherapy (3,5).…”
Section: A C C E P T E D Article In Presssupporting
confidence: 78%
See 1 more Smart Citation
“…No other early post operative deaths were encountered during the study or until the time of writing. The 30-day mortality rate observed in this study is again at least comparable to other similar studies using RF and Cryotherapy (3,5).…”
Section: A C C E P T E D Article In Presssupporting
confidence: 78%
“…None of the patients in this series showed evidence of sepsis, bile duct damage, thrombocytopaenia, or significant systemic upset. This compares very favourably with studies of alternative ablative modalities which have reported complications in up to 33% of the patients treated (3,4). In spite of the fact that some individuals underwent large volume microwave ablations, none of the patients in this study exhibited symptoms similar to that which M A N U S C R I P T…”
Section: Complicationssupporting
confidence: 43%
“…Mortality related to the procedure is low, reported in the literature to be less than 1% [7][8][9] . Tumor type, type of approach, number of lesions, tumor localization, underlying hepatic disease, the physician's experience, associated hepatic resection and lesion size have been described as factors significantly associated with complications [9][10][11][12] . In one of their papers, Poon et al [10] concluded that after the physician's first 50 procedures, the incidence of complications is lower, as well as a shorter hospital stay and higher complete ablation rate.…”
Section: Topic Highlightmentioning
confidence: 99%
“…Intra-abdominal bleeding is the most common complication encountered in many studies [5,6,12,13] . In Mulier's review, it occurred in 0.7% of the procedures in 3670 patients [12] .…”
Section: Hemorrhagic Complicationsmentioning
confidence: 99%
“…Inside the electrode, a closed water circulation system cools the tis- the "low" predictability and the variability of coagulation shape. Accurate prediction of ablation data and geometry are important to prevent local tumor recurrence [15] or collateral damage [16][17][18].…”
mentioning
confidence: 99%